Prospective study of the impact of the Prosigna assay on adjuvant clinical decision-making in unselected patients with estrogen receptor positive, human epidermal growth factor receptor negative, node negative early-stage breast cancer. (23rd April 2015) - Martín, Miguel; González-Rivera, Milagros; Morales, Serafín; de la Haba-Rodriguez, Juan; González-Cortijo, Lucía; Manso, Luis; Albanell, Joan; González-Martín, Antonio; González, Sónia; Arcusa, Angels; de la Cruz-Merino, Luis; Rojo, Federico; et al.
Abstract: Purpose: Improved understanding of risk of recurrence (ROR) is needed to reduce cases of recurrence and more effectively treat breast cancer patients. The purpose of this study was to examine how a gene-expression profile (GEP), identified by Prosigna, influences physician adjuvant treatment selection for early breast cancer (EBC) and the effects of this influence on optimizing adjuvant treatment recommendations in clinical practice. Methods: A prospective, observational, multicenter study was carried out in 15 hospitals across Spain. Participating medical oncologists completed pre-assessment, post-assessment, and follow-up questionnaires recording their treatment recommendations and confidence in these recommendations, before and after knowing the patient's ROR. Patients completed questionnaires on decision-making, anxiety, and health status. Results: Between June 2013 and January 2014, 217 patients enrolled and a final 200 were included in the study. Patients were postmenopausal, estrogen receptor positive, human epidermal growth hormone factor negative, and node negative with either stage 1 or stage 2 tumors. After receiving the GEP results, treatment recommendations were changed for 40 patients (20%). The confidence of medical oncologists in their treatment recommendations increased in 41.6% and decreased in 6.5% of total cases. Patients reported lower anxiety after physicians made treatment recommendations based on the GEP results ( p < 0.05). Conclusions: Though this study does not include evaluation of the impact of GEP on long-term outcomes, it was found that GEP results influenced the treatment decisions of medical oncologists and their confidence in adjuvant therapy selection. Patients' anxiety about the selected adjuvant therapy decreased with use of the GEP.